L’industrie du phosphate de Taïba au Sénégal : front minier et tensions locales - Mouhamadou Lamine Diallo (VertigO, 2017)
The expansion of phosphate mining in the region of Thies, west of Senegal, is a source of territorial reconfiguration and tensions related to the use of natural resources. The advance of the mining front on agricultural areas and the displacement of villages cause the local population to organize and develop strategies to address the impacts of extractive activities. Thus, the article is to analyze these territorial dynamics from Taiba phosphate mining site in the Thies region. It revolves around two points: show the spatial and environmental implications of phosphate mining and analyze the tensions between the mining company, the Chemical Industries of Senegal and local communities.